Predictors for self-reported feeling of depression three months after stroke: A longitudinal cohort study - Janina Kaarre; Tamar Abzhandadze; Katharina S. Sunnerhagen (Medical Journals Sweden, 2021)
Objective: Depression and impaired cognition are common consequences of stroke. The aim of this study was to determine whether cognitive impairment 36-48 h post-stroke could predict self-reported feeling of depression 3 months post-stroke. Design: A longitudinal, cohort study. Patients: Patients aged ≥ 18 years at stroke onset. Methods: Cognition was screened using the Montreal Cognitive Assessment, 36-48 h after admission to the stroke unit at Sahlgrenska University Hospital. Information about self-reported feeling of depression 3 months post-stroke was retrieved from Riksstroke (the national quality register for stroke in Sweden). Bootstrapped binary logistic regression analyses were performed. Results: Of 305 patients, 42% were female, median age was 70 years, and 65% had mild stroke. Three months post-stroke, 56% of patients had self-reported feeling of depression; of these, 65% were female. Impaired cognition at baseline could not predict self-reported feeling of depression 3 months later. The odds for self-reported feeling of depression were twice as high in female patients (odds ratio 2.01; 95% confidence interval, 0.20-1.22; p < 0.01). Conclusion: Impaired cognition early after stroke could not predict self-reported feeling of depression 3 months post-stroke. Compared with male patients, female patients had twice the odds of self-reported feeling of depression